Molecular gas and dust emission in a z = 3.63 strongly lensed starburst merger at sub-kiloparsec scales. Issue Volume 15:Issue S352(2019) (June 2019) - Yang, C.; Gavazzi, R.; Beelen, A.; Cox, P.; Omont, A.; Lehnert, M. D.
Abstract: We present 0.″2–0.″4 resolution ALMA images of the submillimeter dust continuum and the CO, H2 O, and H2 O + line emission in a z = 3.63 strongly lensed dusty starburst. We construct the lens model for the system with an MCMC technique. While the average magnification for the dust continuum is about 11, the magnification of the line emission varies from 5 to 22 across the source, resolving the source down to sub-kpc scales. The ISM content reveals that it is a pre-coalescence major merger of two ultra-luminous infrared galaxies, both with a large amount of molecular gas reservoir. The approaching galaxy in the south shows no apparent kinematic structure with a half-light radius of 0.4 kpc, while the preceding one resembles a 1.2 kpc rotating disk, separated by a projected distance of 1.3 kpc. The distribution of dust and gas emission suggests a large amount of cold ISM concentrated in the interacting region.